Fotografia, individuação e invenção: fabricações poéticas do dispositivo fotográfico - Dirceu da Costa Maués (2022)
This thesis seeks to expand some theoretical discussions about a supposed identity or status of photography, proposing an analysis based on the concepts of individuation, technical object and invention (as one of the genetic cycles of the image) presented by the French philosopher Gilbert Simondon. The research was constituted by a theoretical and practical elaboration that emerged from the questions provoked by an artistic production in continuous development and in a reciprocal movement between theory and practice. The hypothesis raised is that we can have an expanded understanding about the notion of photography from the comprehension of its individuation processes that need to be considered, at least, under three fundamental aspects: in relation to the photographic technical device; in relation to the inventive process between the photographer and the device; and in relation to the interactions between the photographic image itself, as object-image, and the world. Depending on the parameters and their own modes of individuation, we will have a multiplicity of possible individuations of the photographic form. It is in relation to this expanded notion of photography, understood as singular and rich in its multiplicities of forms - in permanent becoming, or in process of individuation - that I try to put into dialogue my poetic experience, based on the production of handmade pinhole cameras and other experiments with the photographic device. Thus, it is possible to think of a diversity of modes of existence that photography can become, including a mode of existence of pinhole photography and its possible implications in a poetics of the photographic device.